Systematic Literatur Review: Adversity Quotient dan Self Efficacy dalam Pembelajaran Matematika - Aan Putra; Muthia Roza (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2020)
Innovation in learning is needed. One of the innovations that can be done is innovation from within students, namely adversity quotient and self-efficacy which can generate interest in learning and improve student learning outcomes. This study aims to conduct a literature review on adversity quotient and self-efficacy and their relation to mathematics learning. The research method chosen in this study is the SLR (Systematic Literature Review) method. Data collection was carried out by documenting and reviewing all articles regarding adversity quotient and self-efficacy published in the 2011-2020 period. The articles used in this study were 30accredited national journal articles obtained from the Google Scholar database using the Publish or Perish application. Based on this research, it was found that adversity quotient and self-efficacy can improve mathematics learning, learning outcomes and learning effectiveness of students.